2018
DOI: 10.4172/2090-7214.1000289
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Education, Poverty, and Resources on Family Planning in Developing Countries

Abstract: Introduction: Developing countries are facing many difficulties due to a rise in population. High fertility rates have posed increased health risks for mothers and child's health, resulting in poor quality of life. According to WHO, approximately 225 million women in developing countries want to limit childbearing but are unable to do because of unmet needs, lack of resources, limited access to family planning (FP) services, religious beliefs, and illiteracy. FP can play an imperious role in stabilizing the is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 17 publications
1
25
0
Order By: Relevance
“…This finding is consistent with previous studies conducted in northwest Ethiopia [ 21 ]. The possible explanation could be that postpartum women in urban areas have been reported to have better access to information regarding family planning and general reproductive and sexual health matters than women who reside in rural setting with poor health services [ 22 ]. This might be the case for the women in the studied population.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with previous studies conducted in northwest Ethiopia [ 21 ]. The possible explanation could be that postpartum women in urban areas have been reported to have better access to information regarding family planning and general reproductive and sexual health matters than women who reside in rural setting with poor health services [ 22 ]. This might be the case for the women in the studied population.…”
Section: Discussionmentioning
confidence: 99%
“…shown that an additional year of schooling increased the probability of choosing an injectable by 0.7 percentage points for women in Nepal [9]. Likewise, other research has also shown that higher education helped to change attitudes and practices towards family planning [15].…”
Section: Discussionmentioning
confidence: 91%
“…Pills and condoms each accounted for 4.6% and 4.2%, while IUDs (1.4%%) and implants (3.3%) continue to have low uptake in the overall picture of contraceptive use mix in the country [2]. While the use of any modern method has plateaued for last 15 non-clinic settings because of its unique method with alternative route of delivery requiring less trained providers and the product being compact, discreet, and easily transportable [4][5][6], potentially transforming the way in which women can access and receive their preferred method of contraception [7]. Sayana Press® is approved by regulatory authorities in more than 40 countries across the world [8].…”
Section: Introductionmentioning
confidence: 99%
“…Since the adoption of the Programme of Action of the International Conference on Population and Development (ICPD PoA) in 1994, the provision of safe, effective, and affordable methods of contraception has been an integral part of the efforts to promote sexual and reproductive health and empower women and girls, particularly in Lowand Middle-Income Countries (LMIC) (3). Access to modern contraceptives has also been shown to contribute to poverty reduction through improvement in educational outcomes and economic opportunities for women and girls (4)(5)(6). Given these extensive benefits, the global community and many national governments have, over the years, undertaken policy actions and made investments to increase access to family planning (FP) services.…”
Section: Introductionmentioning
confidence: 99%